Who Can Respond to Treatment?: Identifying Patient Characteristics Related to Heterogeneity of Treatment Effects - Kaplan, Sherrie H. (Med Care, 2010)
BACKGROUND: Interest in comparative effectiveness research and the rising number of negative or “small effect” trials have stimulated research into differential response to treatment among subgroups of patients. OBJECTIVE: To develop and test the Potential for Benefit Scale (PBS), a composite measure to identify subgroups of patients with differential potential for response to treatment, using diabetes as a model. DESIGN: Cross-sectional and longitudinal cohort study. SUBJECTS AND SETTING: Type 2 diabetes patients (n = 1361) were identified from 7 outpatient clinics serving a diverse population. Of these, 611 completed a 1-year follow-up. MEASURES: To represent patients’ health status, we used the Total Illness Burden Index, the Physical Function Index of the SF-36, the Center for Epidemiologic Studies Depression Scale, and the Diabetes Burden Scale. To represent personality characteristics related to health, we used the Provider-Dependent Health Care Orientation scale. We assessed the contribution of these measures to a composite scale of patients’ potential for treatment response in terms of self-reported medication adherence and glycemic control. RESULTS: Principal components analysis confirmed associations among these measures. The internal consistency reliability of the PBS was adequate (Cronbach α = 0.65). Patients in the lowest versus highest quartile of the PBS reported poorer adherence (18% vs. 55%, P < 0.001) and poorer glycemic control at baseline (mean hemoglobin A1c values: 7.75 vs. 7.39, P < 0.001). Those in the highest quartile of the PBS also were more likely to reach target values for glycemic control (HbA1c <7%) at 1-year follow-up, (adjusted OR = 1.61, P < 0.05). CONCLUSIONS: The PBS, a composite scale, may be helpful in identifying patients with differential potential for response to treatment.